2004
DOI: 10.1111/j.0908-8857.2004.03215.x
|View full text |Cite
|
Sign up to set email alerts
|

Brood rearing costs affect future reproduction in the precocial common goldeneye Bucephala clangula

Abstract: Milonoff, M., Pöysä, H., Runko, P. and Ruusila, V. 2004. Brood rearing costs affect future reproduction in the precocial common goldeneye Bucephala clangula . Á/ J. Avian Biol. 35: 344 Á/351.Life-history theory assumes a trade-off between current reproductive effort and future reproductive success. There are a large number of studies demonstrating reproductive trade-offs in different animal taxa, particularly in birds. Most bird studies have focused on the costs of chick rearing in altricial species. These cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The explanation of why parasites and nesters in the common goldeneye differ in their ability to assess nest predation risk probably lies in the fact that the most valuable information regarding site-specific success is available after the ducklings have left the nest (see Pöysä 2006). And this is the time when successful nesting females are busy with time-consuming brood rearing (Milonoff et al 2004), whereas parasites that do not have their own brood are free from parental duties and, therefore, able to invest more time in nest site prospecting to find safe nests for parasitic laying in the next breeding season (Pöysä 2006). Data to study these aspects are difficult to obtain, but similar results concerning nonrandom nest predation and preference for successful nest sites have been found for other species.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation of why parasites and nesters in the common goldeneye differ in their ability to assess nest predation risk probably lies in the fact that the most valuable information regarding site-specific success is available after the ducklings have left the nest (see Pöysä 2006). And this is the time when successful nesting females are busy with time-consuming brood rearing (Milonoff et al 2004), whereas parasites that do not have their own brood are free from parental duties and, therefore, able to invest more time in nest site prospecting to find safe nests for parasitic laying in the next breeding season (Pöysä 2006). Data to study these aspects are difficult to obtain, but similar results concerning nonrandom nest predation and preference for successful nest sites have been found for other species.…”
Section: Discussionmentioning
confidence: 99%
“…Parental care is one of the major costs of reproduction (e.g. Pettifor, Perrins & McCleery 1988; Jacobsen, Erikstad & Sæther 1995; Milonoff et al. 2004), and for species with extended parental care this will be most acute during the non‐breeding period.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of reproductive costs in goldeneyes has been mixed. Multiple studies have reported no difference in survival rates among females that nested successfully compared to those that failed (Savard and Eadie , Ludwichowski et al ), whereas Milonoff et al () reported a negative effect of brood rearing on future reproductive output. Additionally, Dow and Fredga () reported that first‐time breeding females that laid larger clutches were less likely to be encountered again, suggesting age‐related costs of reproduction (Newton , Viallefont et al ).…”
mentioning
confidence: 99%